BENTUK DAN GAYA PENUTURAN FILM DOKUMENTER BERBASIS BUDAYA DAERAH PB XII: BERJUANG UNTUK SEBUAH EKSISTENSI - D.A, N.R.A. Candra (Seni Media Rekam ISI Surakarta, 2013)
This study aimed to describe the form,narrative style and dramatic flow of the film PBXII: Berjuang untuk Sebuah Eksistensi. So far, to understand the advantages and limitations ofdocumentary film in conveying messages is to divide it into three basic parts of documentaryfilm.Through aesthetic touches on the film, a documentary film director tries to convey thespecial things that became the basic theme of the documentary.IGP.Wiranegara, through workbased culture documentary film, seeks to show the form and style of its own narrative in thetheme of the film.The film is narrated dramatically by the director by give a viewpoint of thestrong character for the characters to show the relation of the content and message of the film.Through picture of the central figure and role model,the figure of a Pakubuwana XII tried hardin order that Surakarta palace still exist as part of the cultural community in Central Java,especially Surakarta (Solo).Keywords:Form,style,movies,documentary, culture,and the region